Constant polarization generation metasurface for arbitrarily polarized light. Issue 25 (16th June 2022) - Sun, Zhanshan; Yang, Kai; Mao, Ruiqi; Lin, Yi; An, Qiang; Fu, Yunqi
Abstract : Polarization generation metasurface that can convert arbitrary polarization to constant polarization. Abstract : State of polarization (SoP) of light is one of the fundamental characteristics of light and has great significance to optical communication, imaging, quantum optics and medical facilities. The generation and maintenance of polarized light have always been research concerns in polarization optics. Polarization-maintaining fibers are frequently used to transmit polarized light without changing its polarization in optical systems, but the high cost and coupling efficiency problems hinder their usage in large-scale light paths. Polarization controllers, which operate arbitrary polarization generation and conversion at the expense of utilizing at least two optical elements such as a half-wave plate and quarter-wave plate, are too bulky for some special applications. Meanwhile, they can only generate desired output polarization of light by transcendentally determining the input polarization, which means that the existing polarization controllers cannot respond in real time. Metasurfaces composed of subwavelength nanoscatterers offer fruitful functionalities to manipulate the amplitude, phase and polarization of light. Here, we propose and experimentally demonstrate a real-time polarization controller realized by combining a depolarizer and polarizer into one monolithic metasurface. Arbitrary polarization states can be transferred to the required polarization with no requirement to determine the incident polarization in advance. Through combining with ordinary optical fibers, the proposed metasurface may also replace polarization-maintaining fibers and optical fiber polarizers in some polarization-dependent applications. This versatile concept may settle the problems of arbitrary polarization conversion once and for all.